THE POLICY DIRECTION OF THE REGIONAL HOUSE OF REPRESENTATIVES OF ACEH TENGAH REGENCY IN THE DISCUSSION OF THE 2025 REGIONAL REVENUE AND EXPENDITURE BUDGET IN THE HEALTH SECTOR IN ACEH TENGAH REGENCY - Edi Kurniawan; Yanhar Jamaluddin; Syafruddin Ritonga (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the policy direction of the Regional House of Representatives of Aceh Tengah Regency (DPRK Aceh Tengah) in the discussion of the 2025 Regional Revenue and Expenditure Budget (APBK) in the health sector in Aceh Tengah Regency. The focus of the study is directed at the policy process of the DPRK in carrying out its budgeting function, as well as the internal and external factors that hinder the implementation of such policies. This study employs a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observations, and documentation involving parties directly engaged in the discussion of the APBK, both from legislative and executive elements. The results of the study indicate that the policy of DPRK Aceh Tengah in the discussion of the 2025 APBK in the health sector has basically been implemented in accordance with the prevailing laws and regulations; however, in practice, it still encounters various obstacles. Internal inhibiting factors include limited human resources, differences in understanding among DPRK internal bodies, and weak technocratic capacity of some DPRK members. Meanwhile, external factors include executive dominance in budget management, limited space for public participation, and the dynamics of political interests in the budget discussion process. Efforts undertaken to overcome these obstacles include enhancing the capacity of DPRK members, strengthening coordination between the legislative and executive branches, and optimizing the supervisory function of the DPRK so that budget policies in the health sector are more oriented toward public interests.